Art from a Fractured Past: Memory and Truth-Telling in Post-Shining Path Peru - Milton, Cynthia (Knowledge Unlatched (KU), 2013)
Peru's Truth and Reconciliation Commission not only documented the political violence of the 1980s and 1990s but also gave Peruvians a unique opportunity to examine the causes and nature of that violence. In Art from a Fractured Past, scholars and artists expand on the commission's work, arguing for broadening the definition of the testimonial to include various forms of artistic production as documentary evidence. Their innovative focus on representation offers new and compelling perspectives on how Peruvians experienced those years and how they have attempted to come to terms with the memories and legacies of violence. Their findings about Peru offer insight into questions of art, memory, and truth that resonate throughout Latin America in the wake of "dirty wars" of the last half century. Exploring diverse works of art, the contributors show that art, not constrained by literal truth, can generate new opportunities for empathetic understanding and solidarity.
Keywords: Andes; Ayacucho; History; Lima; Peru; Retablo; Sacsamarca District; Shining Path; thema EDItEUR::N History and Archaeology::NH History::NHK History of the Americas

Introduction: The Arts of Truth Telling in Post Shining-Path Peru - Milton, Cynthia E. (Art from a fractured past: memory and truth-telling in post-shining path Peru, 2014)
Peru's Truth and Reconciliation Commission not only documented the political violence of the 1980s and 1990s but also gave Peruvians a unique opportunity to examine the causes and nature of that violence. In Art from a Fractured Past, scholars and artists expand on the commission's work, arguing for broadening the definition of the testimonial to include various forms of artistic production as documentary evidence. Their innovative focus on representation offers new and compelling perspectives on how Peruvians experienced those years and how they have attempted to come to terms with the memories and legacies of violence. Their findings about Peru offer insight into questions of art, memory, and truth that resonate throughout Latin America in the wake of "dirty wars" of the last half century. Exploring diverse works of art, including memorials, drawings, theater, film, songs, painted wooden retablos (three-dimensional boxes), and fiction, including an acclaimed graphic novel, the contributors show that art, not constrained by literal truth, can generate new opportunities for empathetic understanding and solidarity

Recovering Memory through Visual Accounts - Milton, Cynthia E. (Art from a fractured past: memory and truth-telling in post-shining path Peru, 2014)
Peru's Truth and Reconciliation Commission not only documented the political violence of the 1980s and 1990s but also gave Peruvians a unique opportunity to examine the causes and nature of that violence. In Art from a Fractured Past, scholars and artists expand on the commission's work, arguing for broadening the definition of the testimonial to include various forms of artistic production as documentary evidence. Their innovative focus on representation offers new and compelling perspectives on how Peruvians experienced those years and how they have attempted to come to terms with the memories and legacies of violence. Their findings about Peru offer insight into questions of art, memory, and truth that resonate throughout Latin America in the wake of "dirty wars" of the last half century. Exploring diverse works of art, including memorials, drawings, theater, film, songs, painted wooden retablos (three-dimensional boxes), and fiction, including an acclaimed graphic novel, the contributors show that art, not constrained by literal truth, can generate new opportunities for empathetic understanding and solidarity

Art from a fractured past: memory and truth-telling in post-shining path Peru - Milton, Cynthia E. (Duke University Press, 2014)
Peru's Truth and Reconciliation Commission not only documented the political violence of the 1980s and 1990s but also gave Peruvians a unique opportunity to examine the causes and nature of that violence. In Art from a Fractured Past, scholars and artists expand on the commission's work, arguing for broadening the definition of the testimonial to include various forms of artistic production as documentary evidence. Their innovative focus on representation offers new and compelling perspectives on how Peruvians experienced those years and how they have attempted to come to terms with the memories and legacies of violence. Their findings about Peru offer insight into questions of art, memory, and truth that resonate throughout Latin America in the wake of "dirty wars" of the last half century. Exploring diverse works of art, including memorials, drawings, theater, film, songs, painted wooden retablos (three-dimensional boxes), and fiction, including an acclaimed graphic novel, the contributors show that art, not constrained by literal truth, can generate new opportunities for empathetic understanding and solidarity

Conflicted Memory: Military Cultural Interventions and the Human Rights Era in Peru - Milton, Cynthia E. (Critical human rights, 2018)
What happens when concepts of "truth," "memory," and "human rights" are taken up and adapted by former perpetrators of violence? Peru has moved from the 1980s–90s conflict between its armed forces and Shining Path militants into an era of open democracy, transitional justice, and truth and reconciliation commissions. Cynthia Milton reveals how Peru's military has engaged in a tactical cultural campaign—via books, films, museums—to shift public opinion, debate, and memories about the nation's violent recent past and its part in it. Milton calls attention to fabrications of our post-truth era but goes further to deeply explore the ways members of the Peruvian military see their past, how they actively commemorate and curate it in the present, and why they do so. Her nuanced approach upends frameworks of memory studies that reduce military and ex-military to a predictable role of outright denial.
Keywords: History / Americas (North, Central, South, West Indies); History / General; History / Latin America / South America; History / Military / General; Political Science / Human Rights; Political Science / World / Caribbean & Latin American; Psychology / Cognitive Psychology & Cognition; Social Science / Violence in Society

Curating memories of armed state actors in Peru’s era of transitional justice - Milton, Cynthia E (Memory Studies, 2015)
Ten years have passed since the Peruvian Truth and Reconciliation Commission (Comisión de la Verdad y Reconciliación) published their findings on the conflict that claimed over 69,000 lives from 1980 to 2000. While the Comisión de la Verdad y Reconciliación placed primary responsibility for deaths and disappearances (54%) on the insurrectionary group Shining Path (Sendero Luminoso), it also named armed state actors as having systematically committed acts of violence. Publicly shamed for their collusion in the corrupt Fujimori government, state security forces initially lent their support to the Comisión de la Verdad y Reconciliación and to the transition to democracy. Yet, over the last decade, armed state actors have appropriated the language, imagery and mechanisms of human rights memory entrepreneurs to advance their own versions of Peru’s recent past which oppose the Comisión de la Verdad y Reconciliación’s findings while highlighting state actors’ heroism. This article examines two such endeavors to reframe this past, the National Police Terrorism Unit (DINCOTE) museum and the Armed Forces Monument to the Heroes of Chavín de Huántar.

Desfigurando la memoria: (des)atando los nudos de la memoria peruana - Milton, Cynthia E. (Anthropologica, 2015)
Este artículo analiza las corrientes opositoras a la memoria colectiva de la sangrienta guerra interna del Perú (1980-2000) a través de un análisis de los actos de vandalismo perpetrados contra uno de los pocos sitios dedicados a la memoria en este país, El ojo que llora, ubicado en Lima. ‘Vandalismo’, en este artículo, es entendido como una forma de escritura (aunque violenta) de una visión distinta del pasado. Originalmente concebido como un espacio para recordar y rendir homenaje a las víctimas del conflicto armado, el sitio se ha convertido en un lugar para la confrontación de formas distintas de asumir el pasado. Como sitio de recuerdo y reivindicación de derechos humanos, y sobre todo como blanco de intentos de desfiguración permanente, El ojo que llora se ha convertido en un escenario en el que la presencia perdurable del pasado —con sus conflictivas tensiones— se hace visible para el público nacional e internacional. Así, se niega el cierre mismo que las narrativas del gobierno quisieran imponer y, por lo tanto, se mantiene el compromiso público con el pasado. Los conflictos en curso sobre el pasado se hacen visibles en este punto en las luchas por establecer una memoria general y, en este proceso, el significado mismo de ‘víctima’ se ve implicado.

The Many Meanings of Poverty: Colonialism, Social Compacts, and Assistance in Eighteenth-Century Ecuador - Milton, Cynthia E. (Stanford University Press, 2007)
This book analyzes the diverse understandings of poverty in a multiracial colonial society, eighteenth-century Quito. It shows that in a colonial world both a pauper and a landowner could lay claim to assistance as the "deserving poor" while the vast majority of the impoverished Andean population did not share the same avenues of poor relief. The Many Meanings of Poverty asks how colonialism shaped arguments about povertysuch as the categories of "deserving" and "undeserving" poorin multiracial Quito, and forwards three central observations: poverty as a social construct (based on gender, age, and ethnoracial categories); the importance of these arguments in the creation of governing legitimacy; and the presence of the "social" and "economic" poor. An examination of poverty illustrates changing social and religious attitudes and practices towards poverty and the evolution of the colonial state during the eighteenth-century Bourbon reforms.
Keywords: History / Latin America / South America; Social Science / Poverty & Homelessness

At the Edge of the Peruvian Truth Commission: Alternative Paths to Recounting the Past - Milton, Cynthia E. (Radical History Review, 2007)
Keywords: =CL

Public Spaces for the Discussion of Peru's Recent Past - Milton, Cynthia E. (Antipoda. Revista de Antropología y Arqueología, 2007)
In the after math of civil conflict and a truth commission into twenty years of violence (19802000), Peru is presently engaged in the difficult task of establishing overarching narratives that provide frameworks for organizing personal and collective memories in the few public spaces available for the discussion of this recent past. This article looks at two public spaces, a series of performative events in Ayacucho duringthe submission of the truth commission's Final Report, and Lima's memorysite, The Eye that Cries. One contentious memory is over who are appropriate victims and heroes to remember.
Keywords: =CL

Images of Truth: Art as a Medium for Recounting Peru's Internal War - Milton, Cynthia E. (A Contracorriente: una revista de estudios latinoamericanos, 2009)
Este trabajo explica cómo el arte relata el pasado y qué pasado es el que el arte decide relatar, analizando las artes visuales presentes en memorias individuales y colectivas del conflicto reciente de Perú (1980-1992). Además, se analizan dos premisas centrales: en primer lugar, el arte actúa como un modo de comunicación; y en segundo lugar, a partir de esta comunicación, podemos complementar nuestra comprensión histórica de la guerra interna que vivió dicho país latinoamericano.
Keywords: aftermath; art; civil; conflict; guerrilla; memories; perú; pictures; visual; war

Poverty and the Politics of Colonialism: “Poor Spaniards,” Their Petitions, and the Erosion of Privilege in Late Colonial Quito - Milton, Cynthia E. (Hispanic American Historical Review, 2005)
In the first weeks of May 1785, several friends and long-term acquaintances came before the royal courts of Quito to testify on behalf of Don Josef Quiñones y Cienfuegos.1 They described in rich detail the wealth Quiñones once enjoyed: several businesses, homes, haciendas, mines near Barbacoas, slaves to work them and to serve his large family, and a gold-trimmed cloak. However, after many years of litigation over his enterprises, and afflicted with ailments, Don Josef now only had the benefit of a small house of little value, two slaves who were part of his wife’s dowry, and no employment. “In sum,” a witness said, “one can understand him as the poorest fellow among noble people [el sujeto más pobre entre gente noble].” In light of his present legal predicaments, coupled with his insolvency, Quiñones and his witnesses worried that justice might be beyond his reach. The crown attorney (fiscal) adjudicating this case agreed, reasoning that pobres were not only beggars with “absolutely nothing” but also those individuals who lacked the means to pursue justice and, because of their poverty, might lose their rights. As such, the courts declared Quiñones “pobre de solemnidad,” solemn poor, so that he might take up his legal cases free of charge. Don Josef Quiñones y Cienfuegos successfully demonstrated his need and his merit as a deserving member of the solemn poor.

Images of truth: rescuing memories of Peru’s internal war through testimonial art - Milton, Cynthia E. (Art from a fractured past: Memory and truth telling in post-shining path Peru, 2014)

Wandering waifs and abandoned babes: the limits and uses of juvenile welfare in eighteenth‐century audiencia of quito - Milton, Cynthia E. (Colonial Latin American Review, 2004)

El arte desde el pasado fracturado peruano - Milton, Cynthia E. (Instituto de Estudios Peruanos, 2018)
La Comisi?n de Verdad y Reconciliaci?n no solo document? la violencia pol?tica de las d?cadas del ochenta y noventa, sino que tambi?n le dio a los peruanos una oportunidad ?nica para examinar las causas y la naturaleza de esa violencia. En El arte despu?s de un pasado fracturado peruano, acad?micos y artistas desarrollan el trabajo de la Comisi?n, argumentando a favor de ampliar la definici?n del testimonio para incluir diversas formas de producci?n art?stica como evidencia documental. Su enfoque innovador en la representaci?n ofrece perspectivas nuevas y convincentes sobre c?mo los peruanos experimentaron esos a?os y c?mo han intentado adaptarse a los recuerdos y legados de la violencia. Los an?lisis abarcan el arte, la memoria y la verdad que resuenan en toda Am?rica Latina tras las "guerras sucias" del ?ltimo medio siglo. Explorando diversas obras de arte, incluidos monumentos conmemorativos, dibujos, teatro, pel?culas, canciones, retablos y ficci?n, as? como una aclamada novela gr?fica, los colaboradores muestran que el arte, no limitado por la verdad literal, puede generar nuevas oportunidades para la comprensi?n emp?tica y solidaria.

La verdad después de 10 años de la Comisión de la Verdad y Reconciliación en Perú - Milton, Cynthia E. (Las luchas por la memoria en América Latina: historia reciente y violencia política, 2016)

Imágenes de verdad: el arte como medio para narrar la guerra interna del Perú - Milton, Cynthia E (A Contracorriente: una revista de estudios latinoamericanos, 2009)
Una mujer camina sola, mientras se limpia las lágrimas de los ojos con una mano. En la otra mano, sostiene distraídamente una hilandera de lana. Uno de sus zapatos está roto. Su espalda está ligeramente inclinada hacia adelante; no por el peso de su bolso, sino de su tristeza. Este dibujo, hecho a lápiz y pastel, se titula “Tras la sombra del dolor” 2. Aunque no hay escenas directas de violencia, el dolor de esta mujer y de su comunidad está inscrito en su cuerpo. Su dolor es visible para nosotros; tal es la capacidad del arte de narrar su experiencia. El arte ofrece un poderoso medio de expresión no verbal. Este artículo se ocupa de las artes visuales en la distribución de las memorias individuales y colectivas del conflicto reciente en el Perú. Dos premisas centrales son la base de esta investigación sobre el arte en el Perú post-Sendero Luminoso: en primer lugar, el arte actúa como un modo de comunicación, y en segundo lugar, a partir de esta comunicación podemos complementar nuestra comprensión histórica de la guerra interna del Perú. Este estudio exige, por lo tanto, ampliar los archivos a fin de incluir otros repositorios de memoria e historia, más allá de los registros producidos por el Estado y escritos 3.

The many meanings of poverty: Colonial compacts and social assistance in eighteenth-century Quito - Milton, Cynthia E. (The University of Wisconsin - Madison, 2002)
This dissertation seeks to understand better colonial society's perceptions of the poor, the social constructions of poverty, and how they changed over the course of the eighteenth century in the city of Quito, capital of the Audiencia of Quito (present-day Ecuador). This study draws from diverse sources from Quito and Spain: ecclesiastical and state records, institutional reports, poverty petitions, and pension requests. Ongoing negotiations between the colonial government and subjects over cultural arguments of poverty and implicit rights and obligations form the central narrative of this study. Two sets of “poor” people emerge as the central protagonists: the economic and the social poor. According to colonial logic, the “wretched,” or miserables—peoples of Amerindian and African descent—were the expected economic poor of labourers and tributaries. Their poverty as such did not contravene the principles underpinning the colonial social structure. The presence of poor Spaniards (in particular American-born creoles), however, contradicted social and normative precepts. One means to fortify failing social structure that gave rise to poor creoles was to offer poor whites institutional and legal assistance not available to other socio-racial groups. Thus, while poverty nipped at the heels of all socio-racial groups, it did not affect all equally. Poverty and classification as “deserving” or “undeserving” of assistance was contingent upon generational, racial, gender, and class considerations. Three overall transformations weakened the colonial compacts regarding poverty. First, the transition from looser Habsburg governance to the administrative centralization of the Bourbon reforms undid tacit accords between the monarch and subject and between the wealthy and the poor. Second, the erosion of the racially defined social hierarchy along with widespread immiseration blurred the boundaries of poverty categories. Third, beneficencia (state-led welfare) superseded charity as state authorities encroached upon church participation in poor relief and the public sphere in general. This dissertation calls for a closer analysis of diversity within the category of “the poor.” Furthermore, this study challenges social control approach to poverty and welfare institutions by considering poor relief in a colonial context and the role of the poor themselves in shaping the many meanings of poverty.
Keywords: =CL; Colonial; Ecuador; Eighteenth century; Poverty; Quito; Social assistance; Social sciences

Muerte en los Andes: los cómics como medio de abordar historias de violencia política en Perú - Milton, Cynthia E. (Cómics y memoria en América Latina, 2019)

Realizing: Studies on the testimony of political violence in Peru (1980-2000) - Milton, Cynthia E. (CAMBRIDGE UNIV PRESS 32 AVENUE OF THE AMERICAS, NEW YORK, NY 10013-2473 USA, 2018)

Espacios públicos para la discusión sobre el pasado reciente del Perú - Milton, Cynthia E (Revista Antípoda, 2007)
Después del conflicto armado interno y una comisión de verdad que investigó los veinte años precedentes (1980-2000), Perú está en el proceso de escribir en espacios públicos las narrativas que proveen las marcas para organizar las memorias individuales y colectivas de este pasado reciente. Este trabajo estudia dos espacios públicos, una serie de eventos en Ayacucho durante la entrega del Informe final de la Comisión de Verdad y el monumento El ojo que llora en Lima. Una de las memorias más conflictivas apunta a quién es la víctima apropiada y el héroe nacional para recordar.

Defacing memory: (Un)tying Peru’s memory knots - Milton, Cynthia E. (Memory Studies, 2011)
This article parses opposing currents in Peru?s collective memory of their bloody internal war (1980?2000) through an analysis of acts of vandalism perpetrated against one of the country?s few sites of memory, the Ojo que llora, in Lima. ?Vandalism? in this article is understood as a form of writing (though a violent one) of an alternative vision of the past. Originally intended as a space for remembering and paying homage to the victims of the armed conflict, the site has become a space for contesting disputed memories. As a site of performance of memory and human rights claims, and especially as the target of continued defacement, the Ojo que llora has become a stage on which the perduring presence of the past ? in its still-conflictual strains ? is made visible for national and international publics. It thus refuses the very closure that government narratives would impose, and thereby keeps open public engagement with the past. The ongoing conflicts over the past made visible at this site point to the struggles to define an over-arching memory, and in the process the very meaning of ?victim? is constrained.
Keywords: =CL

L'allégorie de la justice transitionnelle: résistance à l'oubli et construction du récit mémoriel en Uruguay post-dictatorial - Bérard, Daphné (Université de Montréal, 2021)
In the 1960s, Uruguay endured an economic crisis that quickly turned into a conflict between the National Liberation Movement-Tupamaros (MLN-T) and the state then ruled by Juan María Bordaberry of the Colorado Party. The radicalization of the MLN-T and the rise of State repression granted growing power to the Armed Forces, leading to the coup d'État of June 27, 1973 followed by the establishment of a civic-military dictatorship. The next twelve years were marked by repression, censorship, violence and numerous disappearances. Like other Latin American Cold War dictatorships, Uruguay joined Operation Condor: a South American network led by the United States with the goal of tracking down and annihilating political opponents. The 1985 elections marked the end of the dictatorship and return of democracy. However, in the aftermath of the victory of Julio María Sanguinetti of the Colorado party, a struggle erupted in the heart of society over who was to blame for the country’s fall into authoritarianism, state repression and violence. On the one hand, the Armed Forces were accused of abuse of power and crimes against humanity. On the other, some defended the military as though they had saved the country from the “subversive” threat. This study analyzes Uruguay’s transitional process which, unlike its Latin American counterparts, has not included a formal mechanism for the search for truth upon the return of democracy. Uruguay rather chose to amnesty the Tupamaros detained during the dictatorship, all the while promulgating the Law of Caducity which granted impunity to the military. By collecting different perspectives on the recent past through art and cultural productions produced by civil society after le return du democracy, this thesis studies the evolution of memorial speeches as they are expressed in public spaces. Our goal is to better understand how memorial discourses emerge in a country where democratic remedies have confirmed impunity.
Keywords: Dictatorship; Dictature; Droits de l’homme; Histoire récente; History - Latin American / Histoire - Latino-américaine (UMI : 0336); Human rights; Justice sociale; Memory; Mémoire; Post-memory; Post-mémoire; Recent history; Social justice; Uruguay

La critique maoïste péruvienne face à la Réforme agraire de Velasco (1969-1980) : enquête sur les causes d'une révolution qui ne vint pas - Dorais, Geneviève (Université de Montréal, 2007)
Keywords: Amérique latine; Bandera Roja; Gauche politique; Maoïsme; PC del P; PCP; Patria Roja; Pérou; Réforme agraire; Révolution; Sentier lumineux; XXe siècle

La guerre contre-insurrectionnelle guatémaltèque : sa généalogie, le déni des responsables et les sources historiques - Drouin, Marc (Université de Montréal, 2013)
L’Amérique centrale, théâtre des dernières batailles rangées de la guerre froide, est aujourd’hui la région la plus violente au monde, selon les Nations unies. Notre étude s’intéresse à la forme de guerre irrégulière livrée par l’État guatémaltèque contre sa propre population pendant la deuxième moitié du vingtième siècle. À la lumière de rares témoignages d’exécutants et d’archives militaires et policières, nous examinons un mécanisme clandestin de répression dont les trois principales composantes – les enlèvements, la torture et les exécutions sommaires – pouvaient s’abattre sur toute personne soupçonnée, à tort ou à raison, de conspirer contre un statu quo d’exclusion. Au moment de leur articulation, ces moyens répressifs ont constitué un dispositif qui, à partir de 1966, s’est avéré d’une redoutable efficacité. Arme de prédilection des adeptes de la guerre antisubversive pendant plus de vingt ans, le dispositif permettait, telle une chaîne de production, l’accumulation des renseignements jugés indispensables à cette forme de guerre, ainsi que les cadavres dont l’absence éternelle ou la présence outrageuse sur la place publique servaient d’avertissement funeste à l’ensemble du corps social. Où chercher les origines d’un tel dispositif? À partir des ouvrages de référence cités dans le manuel de guerre contre-subversive de l’armée guatémaltèque, la réponse à cette question nous fera découvrir des parachutistes français pour qui la défaite militaire en Indochine et en Algérie pendant les années 1950 n’était pas une option et pour qui la victoire justifiait absolument tous les moyens. Le penchant de ces pionniers de la guerre hors-norme pour les cours magistraux, les entrevues et les articles, nous a permis d’étudier les méthodes qu’ils préconisaient et de repérer leurs traces au Guatemala. Alors que la guerre qui avait servi de prétexte au maintien du dispositif est terminée, sa très réputée efficacité assure encore aujourd’hui sa pérennité auprès de ceux qui peuvent s’offrir le service. En ce sens, la contre-insurrection se poursuit, et ce, malgré l’absence depuis une quinzaine d’années d’un conflit armé. Cette thèse aborde l’histoire de la guerre irrégulière et son déroulement au Guatemala. Les archives et les témoignages à notre disposition contredisent le déni des crimes commis dans les villes et les campagnes guatémaltèques, dont le génocide de 1982. Finalement, certains signes avant-coureurs indiquent que la violence et l’impunité actuelles au pays pourraient mener à la répétition de tels crimes à l’avenir.
Keywords: Algeria; Algérie; Atrocity crimes; Cold War; Contre insurrection; Counter-insurgency; Crimes de masse; Genocide; Guatemala; Guerre froide; Génocide; History - Latin American / Histoire - Latino-américaine (UMI : 0336); La bataille d’Alger; Perpetrator accounts; The Battle of Algiers; Témoignages d’exécutants

La conversion à la frontière : le cas de Maynas au XVIIIe siècle - Lasnier, Dominic (Université de Montréal, 2007)
Keywords: Amérique latine; Conversion; Jésuites; Maynas; Missions; XVIIIe siècle

Résister à l'exploitation : une histoire de l'opposition péruvienne aux transnationales minières de 1901 à nos jours - Lamarche, Steve (Université de Montréal, 2014)
Throughout the twentieth century, the Peruvian mining industry has undergone a series of transformations that have had profound economical, social and political impact on the nation and its citizens. These changes, however, were not without opposition. In fact, studying recent Peruvian history from a resistance point of view, three different periods come to the foreground. From 1901 to 1930, workers were mostly Andean peasants coerced to work in mines by means of a debt-peonage system called enganche. Their means of resistance, having no union at this time, were mostly individual and short-termed, such as leaving their workplace without completing their contract. One non-governmental organization (NGO) concerned about miners' working conditions was the Asociación Pro-Indígena, composed of progressive Peruvian intellectuals such as Dora Mayer, who studied the practice and impact of the enganche system. The second – spanning from 1930 to 1980 – is both the longest and most important period for studying the transformation of the mining industry and its impact. It is during this period that unions were created and expanded, despite facing serious state oppression. In 1969, the Federación Nacional de los Trabajadores Mineros y Metalúrgicos del Perú (FNTMMP) was created and was the first successful attempt to unite all mining industry workers into one organization. This federation was a prominent actor in the social movement of the seventies, and was one of the organizations that contributed to General Bermúdez's resignation and the presidential elections of 1980 which signaled Peru’s return to democracy after over a decade of military rule. Parallel to this return to representative democracy was the launching of Sendero Luminoso's armed struggle, and the subsequent civil war. This period affected greatly unions of all sectors, who were caught between Sendero Luminoso's purges and the Army's repression. The third period begins with Alberto Fujimori's presidential election in 1990. This president is known for his victory against Sendero Luminoso and the neoliberal reforms he pushed forward by way of quasi-authoritarian practices (such as the suspension of congress in 1992). These reforms mainly consisted in the government changing legislation in order to help foreign companies, such as mining firms, to benefit from Peru's primary resources. Resisting this new paradigm are the communities organized through the Confederación Nacional de las Comunidades Afectadas por la Minería (CONACAMI). Finally, although each period demonstrates distinct means to battle against transnational mining companies and to circumscribe and seek repair for abuses committed, there is a continuity across them: the subalterns' will to be heard.
Keywords: Histoire du Pérou; History - Latin American / Histoire - Latino-américaine (UMI : 0336); Industrie minière; Labor movement; Luttes sociales; Mining industry; Peruvian history; Social conflicts; Syndicalisme; Twentieth century; Vingtième siècle

Une guerre à n’en plus finir : mémoires et récits historiques chez des activistes pour la défense du territoire dans le Guatemala post-conflit - Mailly, Sophie (Université de Montréal, 2019)
If the signature of the Peace Accords in 1996 ended the thirty-six-year internal armed conflict between the State and the guerrillas, the peace in Guatemala remains nonetheless quite relative. After the genocide and the counterinsurgency campaigns, numerous Mayan peoples today are facing new threats related to the arrival of natural resource projects in the country. For many, they are the expression of a war by other means. This M.A. thesis looks into the resorts to the past used by activists mobilized to recover their lands and to protect their territory in the post-conflict period. Indeed, the renewal and the transformation of the violence in times of peace brought some inhabitants of the Ixil area to reflect differently on the recent and distant past. This investigation explores the narratives formulated by these militants and the functions of historical memory as a tool for political advocacy which enables to confront past and present violence. In order to do so, this study first analyzes a book originating from a process for the recovering of historical memory by a group of survivors of the internal armed conflict, then, the resort to historical memory by the inhabitants mobilized for the defense of their lands, and, finally, the role of the new generations within the memory and territorial activism in the Ixil area.
Keywords: Guatemala; History - Latin American / Histoire - Latino-américaine (UMI : 0336); Ixil area; defense of land; défense du territoire; dépossession territoriale; genocide; guerre par d’autres moyens; génocide; historical narratives; memory; mémoire; post-conflict; post-conflit; récits historiques; région ixil; territorial dispossession; war by other means

Chronique, enquête et silence : autopsie de la présentation du conflit interne par la presse de Lima jusqu’au massacre d’Uchuraccay, 1960-1983 - Otis, Louis (Université de Montréal, 2012)
En 2003, la Commission de vérité et de réconciliation du Pérou (CVR) publie un rapport sur la période de guerre interne et de violence qui a déchiré le pays entre 1980 et 2000. Ce rapport étudie ces deux décennies pour faire la lumière sur les événements et évaluer la position de divers secteurs de la société afin que les Péruviens puissent se réconcilier avec un pan de leur histoire. Dans son rapport, la CVR consacre une section aux médias, notamment la presse écrite, et salue le rôle « important » qu’ils ont joué, tout en notant au passage que leur couverture du conflit n’a pas favorisé la pacification du pays et a même pu la compromettre par moments. Ce mémoire vise à étudier la couverture de la guerre interne par les trois quotidiens péruviens les plus importants pour le tirage, Expreso, El Comercio, et La República. Il porte surtout sur la période comprise entre le début des hostilités, le 17 mai 1980, et le massacre de huit journalistes dans le village andin d’Uchuraccay, le 26 janvier 1983. Un regard est également jeté sur l’évolution du journalisme au Pérou depuis les années 1960, marquées par l’élection d’un gouvernement démocratique et aussi par l’instauration d’un régime militaire qui se maintiendra au pouvoir pendant 12 ans. Les bouleversements au cours de cette période difficile expliquent, au moins en partie, le désintérêt initialement manifesté par ces quotidiens, au-delà des différences idéologiques manifestes, à l’endroit des premiers pas du Sentier Lumineux et de sa « guerre populaire ».
Keywords: Caricature; Commission de vérité et de réconciliation (Pérou); Conflit interne péruvien; El Comercio; Expreso; History - Latin American / Histoire - Latino-américaine (UMI : 0336); Journalism; Journalisme; La República; Peru; Peruvian internal conflict; Photographie; Photography; Pérou; Sentier Lumineux; Shining Path; Truth and Reconciliation Commission (Peru)

Laver la patrie de la tache de l’ignorance L’État, les mineurs et les enfants de l’Équateur (1760-1845) - Rompré, Hélène (Université de Montréal, 2011)
La métaphore de la famille a été utilisée, aussi bien à l’époque coloniale qu’à l’époque républicaine, pour illustrer le système politique idéal, la domination d’un groupe privilégié, les parents, sur une population obéissante, les enfants. Cette thèse survole les multiples facettes de la minorité en Équateur à l’époque coloniale et au début de l’époque républicaine (1760-1845), en se penchant sur les stratégies mises en place par l’État pour reléguer à un rang subalterne des individus n’appartenant pas à la catégorie raciale blanche métisse, c’est-à-dire les Indiens, les Noirs, les sang-mêlés, à travers un discours infantilisant. Elle s’intéresse aussi à la résistance d’individus refusant de se percevoir comme des mineurs et qui n’acceptaient pas l’ordre établi, les lois ou les décisions gouvernementales. En se présentant comme des parents compétents et en réclamant la patria potestad, l’autorité légale sur leurs enfants, des adultes considérés comme des enfants métaphoriques dans la grande famille patriarcale, par exemple des femmes, des pères indiens ou même des esclaves d’origine africaine, ont revendiqué plus d’autonomie pour eux, pour leurs familles, ou pour leurs communautés. Les guerres d’indépendance ont donné naissance à une république, la Grande-Colombie, et plus tard à un pays, l’Équateur. La figure symbolique du « parent » n’était plus incarnée par le roi d’Espagne et son appareil bureaucratique. Le système politique avait maintenant plusieurs « pères », membres d’un groupe restreint de Créoles qui, hier encore, se plaignaient d’être infantilisés par les Espagnols tyranniques. Les gens du peuple, en grande partie composé d’Indiens, étaient toujours considérés comme des « enfants » dans la nouvelle république. Comment expliquer que, dans une Nation désormais libre, des pans entiers de la population demeurent sous la tutelle d’hommes blancs? Une justification sera utilisée à répétition pour expliquer ce phénomène : l’ignorance du peuple et le besoin d’encadrement temporaire de celui-ci. Ainsi, s’est construit sur plus d’un siècle un véritable « mythe », celui d’une Nation en émergence où tous les citoyens seraient enfin placés sur un pied d’égalité, d’une Nation propre qu’on aurait nettoyée à l’aide d’écoles et de campagnes d’éducation populaire d’une tache tenace : celle de la Barbarie.
Keywords: Ecuador; History - Latin American / Histoire - Latino-américaine (UMI : 0336); Nation; colonialism; colonialisme; education; esclavage; gendre; genre; indigenous people; nation; peuples indigènes; racism; racisme; republic; république; slavery; society; société; state; Équateur; État; éducation

Négocier l'espace national : l'implication des communautés indigènes dans le processus de construction de la nation bolivienne, 1867-1887 - Tremblay, Guillaume (Université de Montréal, 2009)
Keywords: 19th century; Bolivia; Bolivie; Communauté; Community; Ethnicity; Ethnicité; Indegenous people; Indigènes; Nation; Power relations; Relations de pouvoir; XIXe siècle

Discours sur l'État de la nation : pensée d'État, esprit du capitalisme et nationalisme dans la construction de la Bolivie, 1880-1905 - Tremblay, Guillaume (Université de Montréal, 2017)
Opposing Bolivia and Peru to Chile, the War of the Pacific (1879-1884) stands in Bolivia’s national memory as a humiliating moment, a fracture in the country’s territorial integrity, a bitter defeat. If this defeat left a pungent taste in Bolivian patriot’s mouth, it also signified the effective transition (that would last for decades) from military to civilian government. In fact, while nineteenth century Bolivia is characterized by a slow political, economic and social development – which can be perceived as lagging behind in comparison to its closest neighbors – the War of the Pacific marks a turning point as the weak State starts to grow significantly stronger. We consider this bellicose context as a critical juncture in the development of the Bolivian State, and it represents the starting point from which our thesis commences. Looking back at the quarter of century that begins with the War of the Pacific and that runs until the juridical aftermaths of the Federalist War (1898-1899), we first suggest that this period witnesses a strengthening of the State structured around a formal reinforcement of republican institutions (political parties, elections, etc.). This consolidation is especially evidenced by the development of a powerful pensée d’État expressed along the lines of a modern liberal capitalist democracy. Hence, the State emerging at the end of nineteenth century presents itself as a very restrictive republican democracy in which meshes an economy of capitalist nature – such harmonization becoming possible with the development of a “spirit of capitalism” among the Creole elite. Secondly, we argue that this capitalist republican State allows the emergence of a Bolivian nationalism – mostly inexistent until then – supported by the Creole elite. This nationalism will serve, in return, as a legitimizing cultural tool for the State for which stabilizing and reinforcing the Creole elite’s power remains its chief function. This history of State and national development is not however a history of the institutional evolution of the nation-State in the material sense of the word. It is rather a study of the development of the ideas that allow these institutions to emerge and to be imposed. It is, in other words, an intellectual history of political ideas inscribed in the social. Focusing on the political discourses (electoral speeches, pamphlets, manifestos, scientific literature, pleas, etc.) mobilized and deployed among the Creole elite during the nineteenth century’s last 25 years, it is not specifically the institutions that are studied but the mentalités that support them: pensée d’État, spirit of capitalism, nationalism. Without denying the real and effective agency of the indigenous groups and communities regarding the political, cultural, economic and social transformations that have marked Bolivia’s history, the central idea that supports our thesis is that it is ultimately the State that dictates the country’s political, social and economic agenda. Our work aims to reposition the State as the main changing force in Bolivia at the turn of the nineteenth and twentieth centuries. Through its institutions, its monopoly of legitimate violence, and the pensée d’État that supports it, the State commands all of Bolivia’s society other forces that gravitates in its web of power to adopt a reactive or reactionary position. Despite resistances that lead it to change, despite oppositions that coerce it to bend, the State remains the first and last force for change at the end of nineteenth century and the beginning of the twentieth. This thesis intends to show how this remarkable and singular power apparatus came to life and evolved.
Keywords: Aniceto Arce; Bolivia; Bolivie; Capitalism; Capitalisme; Democracy; Démocratie; Federal War; Guerre Fédérale; Guerre du Pacifique; History - Latin American / Histoire - Latino-américaine (UMI : 0336); Nationalism; Nationalisme; Patriotism; Patriotisme; Republic; République; State; War of the Pacific; État

?` Y, después de la verdad? El espacio público y las luchas por la memoria en la post CVR, Perú - Milton, Cynthia; Ulfe, Maria Eugenia (After Truth. E-misférica, 2010)

Defacing Memory: (Un)tying Peru’s Memory Knots - Milton, Cynthia E. (Curating Difficult Knowledge, 2011)
Lika Mutal, the artist behind one of Peru’s only monuments that attempts an encompassing homage to the victims of their internal war (1980–2000), invited me to walk through the Ojo que llora (The Eye that Cries) (see Figure 9.1) in Lima in March 2008. Some 32,000 stones collected from the Chancay sea on Peru’s central coastline—of which 26,000 bear the name, age, and year of death or date of disappearance of a victim—mark a river-like pathway that spirals in toward an obelisk-shaped rock with an embedded smaller sacred stone (the “eye”) that continuously sheds “tears.” This central rock—intended to represent “the core inside of each person”—holds special significance: it represents “Mother Earth (Pachamama or Madre Tierra) who cries for what has happened to her children” (Cárdenas, 2006). The serpentine paths are meant to resemble the meanderings of rivers; in particular, the artist had in mind the River Huallaga in the Amazon basin and the thousands of victims disappeared in it (ibid.). The quietness of the monument in the otherwise bustling city and the solemnity of the names and ages of victims weighs heavily. Reflection is paramount. To leave, one must wind one’s way back through the paths of names, and thus continue contemplation. The design forces one to walk slowly; one cannot rush through this memorial site.
Keywords: =CL

Introduction: Witnesses to Witnessing - Lehrer, Erica; Milton, Cynthia E. (Curating Difficult Knowledge: Violent Pasts in Public Places, 2011)
What happens when the invisible is made visible, when knowledge relegated to society’s margins or swept under its carpet is suddenly inserted into the public domain? The iconic images of German civilians forced to view the newly liberated Nazi camps, standing at the edges of hastily dug trenches full of emaciated bodies are emblematic of an era in which we have faced not only previously unimaginable episodes of mass violence, but have been consternated by how we might engage with these pasts: who should look, at what, how, and to what end? There is an enduring sense that reluctant publics must be forced to confront horrific realities with which we may be somehow complicit—if only in our desire not to really know.
Keywords: =CL

« Tout [n]était pas si négatif que ça » : les mémoires contestées du duvaliérisme au sein de la diaspora haïtienne de Montréal, 1964-2014 - Belony, Lyns-Virginie (Université de Montréal, 2023)
Political instability in Haiti provided an important backdrop to the election of François Duvalier in September 1957. The new head of state, who soon established an authoritarian dictatorship (notably after 1964) and a hereditary regime (after 1971), justified both his victory and presidency trough a messianic message around the creation of a new Haiti. In the end, the duvalierist regime, stretching close to thirty years, was mostly a period marred by state-sponsored violence. Of the many repercussions of the dictatorship the creation of various Haitian diasporic communities, notably in Montreal, Quebec, during the second half of the 20th century remains one of the most notable. Despite the often critical tone employed by most specialists to make sense of the Duvalier period, Haitians, in Haiti and abroad, have remained divided in their assessment of the authoritarian regime. This doctoral thesis locates the emergence and creation of different collective memory scripts within diasporic communities by focusing on the particular case of the Haitian diaspora in Montreal between 1964 and 2014. By combining an analysis of “traditional” written documents and through the examination oral interviews, this research explores how, at different historical junctures between Quebec and Haiti, this population, marked by its heterogeneity, articulated different visions of the dictatorship in Haiti. This thesis was particularly inspired by the concept of “emblematic memory” advanced by the historian Steve Stern (2004) in his book trilogy which investigated different “memory camps” in post-Pinochet Chile. Our own research contends that the discourses and memories of Duvalierism that were forged within the Haitian diaspora in Quebec did not follow a linear trajectory and fell within a larger project where various conceptualizations of Duvalierist power and its place in Haiti’s national history were contested. It also shows that the very way in which many have understood duvalierism has evolved over time to adapt to new political realities in Haiti and in Quebec. Ultimately, it suggests that any reading of duvalierism, positive or negative, is always located within a broader appreciation (critic) of post-1986 Haiti.
Keywords: =CL; Black studies / Études des noirs (UMI : 0325); Collective memory; Diaspora haïtienne; Diaspora haïtienne au Québec; François Duvalier; Haiti; Haitian Diaspora; Haitian Diaspora in Quebec; Haïti; Histoire orale; Jean-Claude Duvalier; Mémoire collective; Oral History

L'École de Mécanique de la Marine (ESMA) : témoin des luttes de mémoires en Argentine - Dugal, Marie-Christine (Université de Montréal, 2009)
Keywords: Argentina; Argentine; Dictatoship (1976-1983); Dictature (1796-1983); ESMA; Luttes de mémoires; Memories; Memory struggles; Mémoires; NAVY School of Mechanmics; École de Mécanique de la Marine

La transmission intergénérationnelle de la mémoire chilienne du passé récent répressif : de Santiago à Montréal - Nguyen, Tuong-Vi (Université de Montréal, 2010)
Le 11 septembre 1973, un coup d’État orchestré par les Forces Armées chiliennes met fin à trois années de gouvernement socialiste dirigé par Salvador Allende. Augusto Pinochet, à la tête du putsch, installe au pouvoir une violente dictature militaire pour dix-sept ans. Événement synonyme de trauma et instigateur d’une période répressive, ou sauvetage national venant freiner la descente aux enfers socialistes? La mémoire de la société chilienne demeure fragmentée vis-à-vis de son passé récent. Cette étude cherche à définir la transmission intergénérationnelle de la mémoire du passé répressif. Menée sur deux fronts, soit à Santiago et à Montréal, la présente recherche s’applique à établir quelles sont les interprétations du passé récent de la génération « postmémoire », c’est-à-dire des personnes nées peu avant ou durant la dictature. Les représentations, les perceptions, ainsi que les canaux d’apprentissage seront mis en perspective selon le territoire, afin de dégager les discours communs et antagonistes. Prenant assise sur des sources orales, ce mémoire présentera les différentes versions du passé selon vingt-huit témoignages.
Keywords: Agency; Allende; Chile; Chili; Dictatorship; Dictature; Droite politique; Exil; Exile; Gauche politique; History - Latin American / Histoire - Latino-américaine (UMI : 0336); Memory; Mémoire; Pinochet; Political left; Political right; Quebec; Québec

La naturalización de la violencia : damnificados, víctimas y desarrollo en la segunda mitad del siglo XX colombiano - Rodríguez Idárraga, Nicolás (Université de Montréal, 2018)
Cette thèse prend au sérieux le problème de la naturalisation de la « violence », à partir de l'analyse visuelle des photographies du livre classique La Violence en Colombie. Au lieu des acteurs sociaux et des coupables, le seul élément qui se distingue dans beaucoup des photos qui accompagnent le livre est l'idée de la violence comme une catastrophe naturelle. Au moment de la violence des années cinquante, on ne parlait pas des victimes comme c'est le cas aujourd'hui en Colombie. Au lieu de la figure contemporaine de la victime, qui a gagné du poids moral au début du processus de justice transitionnelle, la catégorie habituellement utilisée était celle du survivant, qui était liée aux catastrophes naturelles. Cette thèse vise à historiciser la relation entre l'État et le soin des victimes de la violence. Pour ce faire, j´analyse les archives de la Commission de Réhabilitation de 1959 et le Plan National de Réhabilitation qui commença en 1982. A partir de la lecture des archives je constate que l´idée su survivant reste encore l'agent social utilisé pour canaliser les aides aux « victimes ». Ainsi, au lieu d'espaces de mémoire, on a ouvert des opportunités pour le développement. L'analyse des archives du Plan National de Réhabilitation dans ses dossiers relatifs à la reconstruction des zones touchées par l'éruption du volcan d’Armero (1985) m'a amené à conclure que le processus de construction de l'État ne fait pas de différence entre différents types de tragédies, qu'elles soient supposées « naturelles » ou plus « politiques ». Au contraire, la préparation aux catastrophes devient un point de départ pour faire face aux conséquences de la violence. Ainsi, les savoirs nationales et transnationales accumulés pour que l'État puisse prendre soins des urgences faces aux désastres dites naturelles, ont été utilisés dans l’attention aux personnes violemment déplacées. Au lieu d'un État abstrait et totalisant, ce qui est clair dans la thèse, en ce qui concerne la question de sa relation avec la victime, est que ce que nous connaissons comme «État» correspond effectivement à un ensemble de pratiques. Beaucoup de ces pratiques, bien que présentées dans la vie quotidienne comme impartiales, désintéressées et techniques, impliquent un exercice de dépolitisation continue des histoires de violence. Tel sera d'abord le cas des personnes déplacées des années quatre-vingt et quatre-vingt-dix, dont le soin a été confié au Bureau de l'Assistance en Cas de Catastrophe créé à la suite de ce qui s'est passé en Armero. L'année 1985 a été choisie comme le début officiel de la reconnaissance des victimes par les institutions et la Lois des Victimes, mais c'est aussi l'année où les survivants seront intégrés aux rationalités de l'État dans son processus de construction inachevé. Au même moment où les victimes gagnent leur droit à avoir une histoire et une mémoire, leur dépolitisation est rendue officielle. C'est peut-être pour cette raison, je soutiens, que de nombreuses «victimes de la violence», en particulier celles du déplacement, apparaissent devant le pays sans texture régionale, morale ou historique.
Keywords: 1985; =CL; Armero; Colombia; Colombie; Desarrollo; Desastres; Development; Disaster; Développement; History - Latin American / Histoire - Latino-américaine (UMI : 0336); Memoria; Memory; Naturalisation de la «violence»; Naturalización de la “violencia"; Naturalization of "violence"; Victimas; Victimes de la violence; Victims

Archives, Museums and Sacred Storage: Dealing with the Afterlife of the Truth and Reconciliation Commission of Canada - Milton, Cynthia E; Reynaud, Anne-Marie (International Journal of Transitional Justice, 2019)
The Canadian Truth and Reconciliation Commission (TRC) acquired over 1,200 material submissions through the gifts it received at its events. Though other TRCs mention objects in their records, the gift-giving practice that became central to TRC events in Canada was unprecedented, and so is its large collection of TRC-gifted objects today. The Canadian TRC is thus unique and faces the challenges of categorizing, preserving, displaying and honouring these material artefacts. What has been the post-TRC life of these objects and art pieces? What is their role in creating a collective memory of residential schools and how might they promote reconciliation? This article shows that the post-TRC life of the objects opens up new museological spaces and practices through the ways the objects are curated (or not) for remembering and learning about residential schools according to Indigenous protocols and ways of thinking and feeling.

Counting Heads: Race and Non-Native Tribute Policy in Colonial Spanish America - Milton, Cynthia E; Vinson, Ben, III (Journal of Colonialism and Colonial History, 2002)

Art as Remembrance and Trace in Post-Conflict Latin America - Milton, Cynthia E. (Art as a Political Witness, 2017)
One of the foundational stories in the discipline of art history is that of the Corinthian Maid. 1 According to the tale, as told around 77 AD by the Roman natural philosopher Pliny the Elder, a Corinthian potter’s daughter traced on the wall her lover’s shadow, cast by candlelight. The soldier was about to leave for war and his future was uncertain. Moved by the sadness of his daughter upon the soldier’s departure, the father made a sculpture of the young man, based on the drawing that she had done. In art, this technique is that of the trace or indexical sign of what once was present. In Latin America, after the decades of Cold War, civil wars, military incursions and dictatorships, this trace is known as the silhouette, the outline of a loved one disappeared, in most cases, by the state, which grew into the siluetazo, a movement to demand their return. 2 Yet, while similar in technique, the meaning of the act of tracing differs slightly. The Corinthian woman made a reproduction of her lover in anticipation of longing, and possibly in anticipation of the profound sorrow upon his loss. As art historian Lisa Saltzman notes, this story is of “a daughter
Keywords: Political Science / General; Political Science / History & Theory; Political Science / Political Process / General

Chapter Forty-Six Art as Remembrance and Trace in Post-Conflict Latin America (2016) - Milton, Cynthia E. (Posthumanism in Art and Science: A Reader, 2021)
Keywords: =CL

La verdad después de 10 años de la Comisión de la Verdad y Reconciliación en el Perú - Milton, Cynthia E. (Las luchas por la memoria en América Latina: historia reciente y violencia política, 2016)

Fraternité et métaphore familiale : la Révolution française et la Grande-Colombie - Van Hooren, Justin (Université de Montréal, 2007)
Keywords: Fraternité; Indépendance latino-américaine; Pacte social; Révolution française; Révolutions atlantiques

Curating difficult knowledge: violent pasts in public places - Lehrer, Erica T.; Milton, Cynthia E.; Patterson, Monica (Palgrave Macmillan Memory Studies, 2011)

The Truth Ten Years On: The CVR in Peru - Milton, Cynthia E. (The Struggle for Memory in Latin America: Recent History and Political Violence, 2015)
In the hot morning sun on August 29, 2003, the central plaza of Huamanga (Ayacucho) began to fill with Peruvians from many parts of the country, awaiting a report that would tell them about what they had lived through. As midday approached, the heat was sweltering and there was hardly any room to move. Vendors sold ice cream and bottles of water to keep cool the fairly peaceful crowd. Then the commissioners filed onto a stage, symbolically shaped like the local art form of a retablo. The president of the truth commission, Dr. Salómon Lerner, began his speech evoking reciprocity, stating that the truth commissioners had listened to Peruvians for the last two years about the preceding twenty years of violence, and now it was time for them, the commissioners, to return to the audience what they had heard (Lerner Febres 2004, 163–4).
Keywords: 20th century; Collective memory; History; Latin America; Political violence; Politics and government

Curating difficult knowledge: Violent pasts in public places - Lehrer, Erica; Milton, Cynthia E.; Patterson, Monica Eileen (Palgrave Macmillan Memory Studies (PMMS), 2011)
Keywords: =CL

The Art of Truth-telling about Authoritarian Rule - Bilbija, Ksenija; Fair, Jo Ellen; Milton, Cynthia; Payne, Leigh (University of Wisconsin Press, 2005)
People who have lived through authoritarian rule have stories to tell. They want to tell their truths: truths that have been silenced, truths that have been censored, truths that are still uncomfortable. But how do individuals begin to speak about a political past that was too horrible for words, especially when the words only came in torrents of pabulum, snake oil, and venom? How are versions of events that have slipped outside of official narratives best voiced in a society moving out of authoritarianism? This generously illustrated volume examines the art of truth-telling and the creation of stories, accounts, images, songs, street theater, paintings, urban designs, and ideas that pay witness to authoritarian pasts. This comprehensive collection, with contributions by scholars, activists, and artists from around the world, explores this theme across a range of national experiences, each featuring its own unique set of historical, institutional, and cultural conditions. This book is bold, creative in form and content, and unlike any other treatment of authoritarian transitions, with the editors and contributors daringly staking a place for cross-disciplinary conversations on modern history, creative art, politics, and social meaning. By examining the truths--both official and unofficial--about the past, we can learn how to avoid repeating atrocities in the future.
Keywords: Art / General; Art / History / General; Political Science / Comparative Politics; Political Science / General; Political Science / Political Ideologies / Fascism & Totalitarianism; Psychology / General; Psychology / Interpersonal Relations

Artistic Silhouettes - Tortell, Philippe Daniel; Turin, Mark; Young, Margot; Milton, Cynthia E. (Memory, 2018)

Promoting Peru: Tourism and Post-Conflict Memory - Milton, Cynthia; Ulfe, Maria Eugenia (Accounting for Violence: Marketing Memory in Latin America, 2011)
Travel advertisements invite youthful backpackers or the wealthy older set who can travel in comfort to explore the Andes and the highland peoples: guidebooks and documentaries portray images of llamas chewing in highland pastures, rural folk wearing ponchos, majestic ancient civilizations and remaining ruins, all in the scenic setting of jagged, snow-capped mountain peaks.¹ Year after year, hundreds of thousands of tourists visit Peru in search of an Andean experience and adventure. For most, this means visiting Cusco and the newly named, in 2007, world wonder Machu Picchu, walking a few days on the Inca Trail, and spending a brief
Keywords: =CL

Death in the Andes: comics as means to broach stories of political violence in Peru - Milton, Cynthia E. (Comics & memory in Latin America, 2017)

Les droits de la personne - Milton, Cynthia; Pearl, Eliadis; Gilabert, Pablo; Mégret, Frédéric; Provost, René (Le monde d'après: de la covid longue sur les relations internationales, 2023)

Diverse perspectives on interdisciplinarity from Members of the College of the Royal Society of Canada - Cooke, Steven J.; Nguyen, Vivian M.; Anastakis, Dimitry; Scott, Shannon D.; Turetsky, Merritt R.; Amirfazli, Alidad; Hearn, Alison; Milton, Cynthia E.; Loewen, Laura; Smith, Eric E.; Norris, D. Ryan; Lavoie, Kim L.; et al. (FACETS, 2020)
Various multiple-disciplinary terms and concepts (although most commonly “interdisciplinarity,” which is used herein) are used to frame education, scholarship, research, and interactions within and outside academia. In principle, the premise of interdisciplinarity may appear to have many strengths; yet, the extent to which interdisciplinarity is embraced by the current generation of academics, the benefits and risks for doing so, and the barriers and facilitators to achieving interdisciplinarity, represent inherent challenges. Much has been written on the topic of interdisciplinarity, but to our knowledge there have been few attempts to consider and present diverse perspectives from scholars, artists, and scientists in a cohesive manner. As a team of 57 members from the Canadian College of New Scholars, Artists, and Scientists of the Royal Society of Canada (the College) who self-identify as being engaged or interested in interdisciplinarity, we provide diverse intellectual, cultural, and social perspectives. The goal of this paper is to share our collective wisdom on this topic with the broader community and to stimulate discourse and debate on the merits and challenges associated with interdisciplinarity. Perhaps the clearest message emerging from this exercise is that working across established boundaries of scholarly communities is rewarding, necessary, and is more likely to result in impact. However, there are barriers that limit the ease with which this can occur (e.g., lack of institutional structures and funding to facilitate cross-disciplinary exploration). Occasionally, there can be significant risk associated with doing interdisciplinary work (e.g., lack of adequate measurement or recognition of work by disciplinary peers). Solving many of the world’s complex and pressing problems (e.g., climate change, sustainable agriculture, the burden of chronic disease, and aging populations) demands thinking and working across long-standing, but in some ways restrictive, academic boundaries. Academic institutions and key support structures, especially funding bodies, will play an important role in helping to realize what is readily apparent to all who contributed to this paper—that interdisciplinarity is essential for solving complex problems; it is the new norm. Failure to empower and encourage those doing this research will serve as a great impediment to training, knowledge, and addressing societal issues.
Keywords: =CL